5 - Indexing for Communication Journals in Africa: The global knowledge economy and the politics of knowledge distribution - Peter Ogom Nwosu, (Africa Media Review, 2006)
Globalization, the attempt by organizations to expand beyond their domestic boundaries in a manner that assures social and cultural integration, is shaping and reshaping how knowledge is constructed, produced, and distributed in the international arena. Informatization, the utilization of advancements in communication and information technologies, while altering individual lifestyles and the cultural landscape of many societies, has also hastened the pace of globalization. How to become a part of this evolving global knowledge economy has been the focus of discourse among scholars involved in the knowledge industry in different global regions. This essay explores attempts by African scholars to integrate ‘African knowledge’ into the evolving global knowledge economy. Through the work of the Council for the Development of Social Science Research in Africa, this essay also examines the politics, challenges and promises of ‘internationalizing’ knowledge.